Influence of the sagittal inclination of the tibial plateau on the knee joint stability - Golovakha, Maksim; Krasovskiy, Vasil; Gorelov, Oleksandr; Titarchuk, Rostyslav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The effect produced by a change in the anteroposterior inclination of the tibial plateau on the knee joint stability and a displacement of the contact loading area on the inner tibial process was experimentally analysed. Two cadaver preparations of the knee joint served as the material. A change of the tibial plateau inclination in conditions of corrective osteotomy has steady influence on the knee joint kinematics. In case of an injury of the anterior crucial ligament against a background of medial gonarthrosis it is possible to use closed wedge osteotomy in combination with a decreased retrad inclination of the tibial plateau, thereby compensating to some extent for anterior instability of the knee joint. An increased retrad inclination of the tibial plateau results in an anteriad displacement of the tibia and can be used to compensate for posterior instability.